Impacts of Hijab Materials Trades to Economic Improvement of Muslim Youth in Keffi LGA Nasarawa State-Nigeria - Aliyu Ibrahim Musaddad; Dr. Auwal Ahmad Ismail; Dr. Kambari Aminu Muallimu (Journal of Islamic Business and Economic Review, 2021)
ABSTRACTIt is clear that for the former epoch, Nigeria government has been careworn for active economic development tactic, which many administrative cum with it new measurement on economic downstream. This significant occurrence concretes the researcher sight to explore the role of hijab materials business in economic development in Nigeria, with particular reference to Muslim Youth in Keffi Local Government. Hence, the role of youth on economic development cannot be over emphasised, similarly the wheel of development of any country lies on the shoulder of how productive and creative the youth populations are. Though, this study set specific objectives to achieve and explored, various Perceptions, conception and view on roles of hijab in economic activities. Also, the study dependent on qualitative research which is based on both Primary and secondary data, such as document, seminars and other relevant sources related to the study. Finally, the study recommends amongst other that, government should improve its loan scheme to micro business owner in order to economically oversees the wellbeing of their business. Also create channel of awareness among its youth, to observe their views and contribution towards economic development of the country as forthcoming leaders and parents and Religious leaders must not concede to educate their children on the importance of wearing hijab according to the teaching of prophet Muhammad (SAW).